Doing it together. Cooperation tools for the city co-governance. - Sobral, Laura (ZK/U Press, 2019)
'Doing it Together' is about tools for the co-governance of public spaces and strategies for inclusive neighborhood management. The book presents examples of co-governance tools existing in Lisbon, Bologna, and Madrid, together with the Berlin cooperation context [Tempelhofer Feld, Prinzessinnengärten, Haus der Statistik]. 'Doing it Together' is an outcome of Laura Sobral's research and advocacy project as a German Chancellor Fellow with the Alexander von Humboldt Stiftung, which Laura spent in collaboration with ZK/U Berlin.
Keywords: Stadtraum; Öffentlicher Raum; Raumnutzung; Urban Governance; Bürgerbeteiligung; Kooperation; Gemeinschaftsnutzung; Partizipation; Co-Governance